Ecological Turn in Tones of Studio Ghibli’s On Your Mark - Pasopati, Rommel Utungga (Mezurashii: Journal of Japanese Studies, 2024)
This article explores the idea of ecological turn in tones of one of animation by Studio Ghibli entitled On Your Mark published in 1995. The story is about a raid of a cult in which there is an angel being detained. Later, two policemen recued the angel and set her free. Through qualitative method and explorative approach, this paper accentuates matters of ecological turn as seen in the symbols of symbiocene including redefinition of progress in modern era, changing aspect from anthropocene to symbiocene, and the shift of humanism to rely more on nature beings and/or ecocentric surroundings. The tones of this animation indeed show the crucial aspects of ecological issues, such as shift from darkness to light, the signs of bright colors, and the rescue from such dominated power to positive freedom. In conclusion, this animation contains ecological turn in its tones regarding to ambience that point out to ecocentrism than anthropocentrism.